BOOK REVIEW: ENGLISH L2 READING: GETTING TO THE BOTTOM (4TH EDITION) - Huang, Yueyue; Li, Keru (LLT Journal: A Journal on Language and Language Teaching, 2022)
Research in L2 reading, especially the incorporation of insights from reading processing into reading instruction, has gained a standing attention in ELT and recent second language acquisition research has highlighted a complex and dynamic trajectory of reading efficacy development. English L2 Reading: Getting to the Bottom, now in its fourth edition, has timely responded to the psycholinguistic turn in reading studies over decades. With purposefully modified and updated sections on metalinguistic awareness in terms of pedagogical value, the latest edition provides a focused overview of central issues in understanding L2 English reading processors with practical considerations on their direct relevance to pedagogical interventions. This book review will firstly present a brief account of each chapter's underlying concerns and then offer critical comments on the latest version's theoretical implications in relation to current trends in L2 instruction research.